FUTURE SKILLS, NOW UTHM-UNU INTERNATIONAL CLASSROOM 2024 - Chee-Ming Chan (2026)
This publication commemorates the first-ever joint international classroom between Universiti Tun Hussein Onn Malaysia (UTHM) and Universitas Nusa Utara (UNU), Indonesia- a milestone collaboration now archived in this volume.This book brings together key lectures and reflections that celebrate the essence of this pioneering academic partnership. Conducted fully online, the classroom saw full participation from students of both institutions across the Java Sea, embodying the spirit of shared learning without borders.Five inspiring lecturers from UTHM and UNU Yogyakarta shared their expertise through a series of thought provoking sessions on the following topics:• Mr. Berli Arta [UNU Yogyakarta]: Present Like a Pro:Wow the Audience (presentation skills)• Prof. Ir. Dr. Chee-Ming Chan [UTHM]: Rise & Shine: No More Stress (stress management)• Mr. Khunul Harsul Lisan [UNU Yogyakarta]: Unlocking Your Potential: The Power of Self-Discovery and Growth (self-growth)• Assoc. Prof. Ts. Dr. Nor Haslina Hashim [UTHM]: Super Timekeeper: Make Every Minute Counts (time management)• Ms. Rahayu Rziky [UNU Yogyakarta]: Mastering the Art of Effective Presentation: A Guide for University Students (presentation skills)Offering a refreshing break from conventional lectures, the International Classroom empowers students to embrace learning as a journey of growth, curiosity and discovery, preparing them to navigate the future with confidence and purpose.